Enhancing Fourth Grade IPAS Concept Comprehension through Scientific Reading-Based E-Modules Developed with Exe-Learning - Ning Dainty Restiani; Kartika Chrysti Suryandari; Ratna Hidayah (STAI Hubbulwathan Duri, 2024)
The integration of technology in 21st-century learning is essential, particularly in science education, where interactive tools can enhance students' understanding of complex concepts. Exe-learning, a platform that supports the creation of interactive educational content, offers features such as quizzes, practice questions, and simulations that aid in concept comprehension. This study employed a Research and Development (RD) approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) to create an interactive electronic module for the IPAS lesson on